Lexical recognition processes in L2-dominant bilingualism - Bruggeman, Laurence; Cutler, Anne (Frontiers in Language Sciences, 2024)
To comprehend speech, listeners must resolve competition between potential candidate words. In second-language (L2) listening such competition may be inflated by spurious activation; the onsets of 'reggae' and 'legacy' may both activate 'leg' for Japanese listeners, or the rhymes of 'adapt' and 'adept' may activate 'apt' for Dutch listeners, while only one in each pair triggers competition for L1 listeners. Using eyetracking with L2-dominant bilingual emigrants, we directly compared within-language L1 and L2 lexical activation and competition in the same individuals. For these listeners, activation patterns did not differ across languages. Unexpectedly, however, we observed onset competition in both languages but rhyme competition in the L2 only (although the same stimuli elicited rhyme competition for control listeners in both languages). This suggests that L1 rhyme competition may disappear after long-time immersion in an L2 environment.